Aquatic geochemistry of barium in basaltic terrain, Iceland - Naimy, Golnaz 1967- (2008)
The present study focuses on barium, its objective being to quantify the processes that control its concentration in ground waters in the basaltic environment in Iceland. It is based on over 300 samples. The concentrations of Ba in ground waters and <150°C waters from low-temperature geothermal fields in Iceland are highly variable, ranging from <0.01 ppb to about 300 ppb. The average Ba concentration in selected Icelandic basalts is 75 ppm. Aqueous Ba concentrations increase with increasing chloride content of the water. Barium occurs largely as free Ba+2 ion, being over 98% in two-thirds of the samples analyzed and always >92%. All waters are strongly witherite under-saturated. Most of the sampled waters are also barite under-saturated. Yet waters with chloride concentrations above 100 ppm tend to be close to saturation as are some waters of mixed cold- and geothermal water origin. In these waters samples barite solubility controls aqueous Ba concentrations. A correlation is observed between the activities of Ba+2 versus K+. It is known that Ba substitutes for K in K-bearing rock-forming minerals due to the similar size of the Ba+2 and K+ ions. It is considered that aqueous Ba concentrations in barite under-saturated waters are controlled by exchange equilibria between Ba+2 and K+ in secondary K-bearing minerals or possibly by adsorption of Ba+2 onto clay mineral surfaces where it competes with K+ and other ions. Neither was a correlation found between Ba concentration and temperature nor Ba concentration and pH of the samples. Calculations in this study show a clear order in the relative mobilities of the cations of interest. Their mobility is in this order: Na > K > Ca > Ba > Mg > Sr.